SENAM IRAMA PADA KEMAMPUAN MOTORIK KASAR ANAK USIA DINI - Darmawati, Darmawati; Sudarti, Sudarti; Maulina, Iin (Pascasarjana Universitas Pendidikan Ganesha, 2025)
The low gross motor skills of early childhood children are evident in the lack of coordination, balance, and agility in performing daily physical activities. This condition indicates the need to implement effective, engaging learning methods, such as rhythmic gymnastics, to stimulate children's gross motor development optimally. The purpose of this study was to analyse rhythmic gymnastics on the gross motor skills of young children. This study used a qualitative, descriptive approach. The subjects were teachers and children in group B at an early childhood education institution. Data collection methods were through observation, interviews, and documentation. Data analysis techniques used qualitative descriptive analysis. The results of the study showed that rhythmic gymnastics planning was carried out systematically, with attention to the characteristics of early childhood development, including the selection of songs and movements, and an enjoyable and educational activity flow. Rhythmic gymnastics was implemented regularly and actively involved children through movements in time with the music, helping develop their balance, coordination, flexibility, and muscle strength. Teachers evaluated the activity closely, paying attention to the process and outcomes of children's participation, and this evaluation served as a basis for improving subsequent activities.